Flexible assessments as a tool to improve student motivation: an explorative study on student motivation for flexible assessments - Kessels, Giel; Xu, Kate; Dirkx, Kim; Martens, Rob (Frontiers in Education, 2024)
Giving student choices during learning and assessment can be seen as a way to improve perceived autonomy and student motivation for learning and assessment. Autonomy is more than offering choices, rather it is about the autonomy that students actually experience. An increase of autonomy and motivation leads to more fun in learning and deeper learning. Providing choices during assessment -also referred to as flexible assessments- in order to enhance students’ motivation for working on assessment tasks has not been researched extensively. Research on the topic of flexible assessments in order to enhance student motivation is valuable because motivation is the start for learning and assessments can serve as a starting point for learning. This study focuses on what choices in assessments students want to make in order to enhance their motivation. A flexible assessment can enhance students’ perceived autonomy and thereby contribute to more intrinsic motivation for working on these assessment tasks. The study took place in the context of Vocational Education and Training (VET) and consists of two approaches. A cross-sectional survey study to find out on what assessment characteristics students prefer to have choice on. Focus group interviews are used to gain more understanding on how such assessment choices should be designed according to the interviewed students. The participated students preferred to make choices in the moment of assessment, in the number of attempts and in the assessment form. The interviewed students suggested an increase in number of choice options and ownership in choice making decisions during their study. They would like to be coached by their teachers in the decision-making process and, as their study progresses, the guidance of their teacher should decrease. Giving students choice in assessment in order to support their perceived autonomy and thereby contribute to their intrinsic motivation is quite unanimously perceived as positive.